How and Why Was Domesday Made?*. (22nd December 2020) - Baxter, Stephen
Abstract: This article offers a new interpretation of the Domesday survey, drawing upon a collaborative study of its earliest surviving manuscript, Exeter Cathedral Library MS 3500 (Exon). It identifies five principal stages: first, the survey was launched at Gloucester in midwinter 1085; secondly, fiscal information extracted from geld assessment lists was integrated with manorial detail supplied by landholders to create a survey organised on a geographical plan by hundred; thirdly, this hundredal recension was checked by a second group of commissioners at meetings of shire courts, generating a substantial corpus of contested matter; fourthly, the hundredal recension was restructured into circuit returns which grouped together and summarised the holdings of barons who held directly from the king; fifthly, Domesday Book itself was written directly from these circuit returns. Royal assemblies held at Easter, Whitsun and Lammas functioned as deadlines for the second, third and fourth stages respectively; and a major geld levied at the rate of six shillings to the hide was collected and accounted for during this period. The survey generated a range of different outputs, each intended to serve specific fiscal and political purposes: the hundredal recension was designed to facilitate a reassessment of geld liabilities; the lists of contested matter anticipated a later judicial review; the circuit returns, summaries and Domesday Book were designed to make the administration of the royal demesne and the profits of royal lordship more efficient. The latter also supplied barons with what amounted to confirmation charters of their uncontested holdings, for which they performed homage.